Draft Annual Plan 1993-94 Part-II (Statements) Government of Arunachal Pradesh - Planning Commission (Planning Commission, 1993)
Government of Arunachal Pradesh Progress of Expenditure during Annual Plans 1991-92 & 1992-93 and proposed outlay for the Annual Plan 1993-94 Physical Targets Achievement during the Annual Plans 1991-92 & 1992-93 and proposals for the Annual Plan 1993-94.
Government of Arunachal Pradesh
Government of Arunachal Pradesh Planning and Development Department Itanagar
Keywords: Government of Arunachal Pradesh; Planning and Development Department; Annual Plan - 1993-94; Progress of Expenditure during Annual Plans 1991-92 & 1992-93; Proposed outlay for the Annual Plan 1993-94 Physical Targets Achievement during the Annual Plans 1991-92 & 1992-93; Proposals for the Annual Plan 1993-94; Proposals for Spill over and ongoing Progrramme; Maximizing Benefits of completed Progrramme/projects; Centrally Sponsored Schemes; Outlays and expenditure Minimum Needs Progrramme